HAK UNTUK MELAKUKAN UPAYA HUKUM OLEH KORBAN KEJAHATAN DIKAJI DARI KITAB UNDANG-UNDANG HUKUM ACARA PIDANA INDONESIA - Paramaningrat Manuaba, Ida Bagus; Ari Yuliartini Griadhi, Ni Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
The paper is titled " The Right To Take Legal Actions By Victims Of Crime Reviewed From The Indonesian Book Of The Law Of Criminal Procedure." This paper uses normative analytical methods and statute approach. Indonesian the book of the law of criminal procedure law gives right to suspects that they can do legal actions like apeal, casation, and then until judicial review. On the other hand, the law give now right to do the legal actions to the victims because they have to be representation by public prosecutor. This term make unfair to the victims because they have no right that the law gives to the suspects. Hence it is necessary to revise the law with a view to equal the right between the victims and the sucpects in terms of legal actions.
Keywords: Victims, Right, Criminal Procedure Law, Legal Actions